Comprehensive Clinical Assessment of Vestibular Function in Multiple Sclerosis. Issue 3 (July 2021) - Cochrane, Graham D.; Christy, Jennifer B.; Motl, Robert W.
Abstract : Background and Purpose: Balance disorders and dizziness are common in people with multiple sclerosis (MS), suggesting dysfunction of the vestibular system. Evaluating how people with MS perform on objective clinical vestibular tools will help broaden understanding of vestibular function in MS. This cross-sectional study's goal was to complete a robust battery of vestibular-ocular reflex (VOR), dynamic visual acuity (DVA), subjective visual vertical (SVV), and cervical and ocular vestibular-evoked myogenic potential (c/oVEMP) tests in people with and without MS. Methods: Forty people with relapsing-remitting MS (Expanded Disability Status Scale [EDSS] ⩽6.5) and 20 controls completed the vestibular testing battery. Results were compared between groups and correlations with EDSS scores were calculated. Results: People with MS were less able to visually cancel their VOR and showed a larger variance in response on SVV. EDSS significantly correlated with VOR cancellation, SVV variance, and DVA lines lost; linear regression showed that VOR cancellation and SVV variance significantly predicted EDSS. Discussion and Conclusion: Vestibular functions requiring central integration of vestibular information, but not reflexive vestibular functions like VEMP, were impaired in people with MS and correlated with EDSS, suggesting that clinical evaluation of functions requiring central integration best evaluates MS-related vestibular dysfunction. Measures assessing central vestibular integration and not vestibular reflexes may be more sensitive to detecting vestibular deficits in people with mild to moderate MS. Video Abstract available for more insight from the authors (see Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A344 ). Abstract : Supplemental Digital Content is Available in the Text.